Composition Of Mangrove Species On Ngurah Rai Mangrove Forest Pemogan Village, Denpasar Selatan District, Denpasar Municipality, Bali Province - Anak Agung Ketut Darmadi; I Putu Gde Ardhana (Jurnal ILMU DASAR, 2010)
The research on analysis of composition of mangrove forest vegetation is a fundamental that can be used toutilize mangrove forest. The research was carried out at Ngurah Rai Mangrove forest, Pemogan village,Denpasar Selatan district, Denpasar Municipality, Bali province be using systematic plot sampling method. Theresearch result showed that there are seven kinds of mangrove tree found, such as Soneratia alba (L.) Blanco,Rhizophora apiculata BL., Avicennia alba Blume, Bruguiera gymnorrhiza (L.) Lamk., Xylocarpusmoluccensis (Lam.) M. Roem., Aegiceras corniculatum (L.) Blanco, and Ceriops tagal (Perr.) C.B. Robinson.Number of S. alba (L.) Blanco growth increase from sea to land. The highest important value was found in S.alba (L.) Blanco.